Implementation of Six Sigma DMAIC Methodology for Eliminating Spot Crack Defects in Automotive Resistance Spot Welding Process - Reza Febriyana; Heru Darmawan; Rani Rahmadiyani (Immortalis Journal of Interdisciplinary Studies, 2026)
Automotive welding processes require high process stability because welding defects directly influence product reliability and manufacturing cost. This study investigates the reduction of spot crack defects in an automotive Rear Door welding process using the Six Sigma DMAIC (Define–Measure–Analyze–Improve–Control) methodology. A quantitative case study approach was applied by integrating defect analysis, process capability measurement, Pareto analysis, Fishbone analysis, and corrective action implementation. The initial assessment identified 20 spot crack defects from 2,400 production units, resulting in a DPMO value of 2,083.33 and a process capability level of 4.37 sigma. Root cause analysis revealed that the defects were mainly associated with insufficient operator knowledge, unstable welding gun positioning due to damaged gun shanks, limited inspection coverage, and the absence of welding position control. Improvement actions included operator retraining, equipment replacement, additional inspection points, and implementation of a welding gun guide fixture. After improvement implementation, monitoring of 2,380 production units showed zero spot crack defects, achieving a DPMO value of 0 and process capability above 6 sigma. The findings demonstrate that a structured Six Sigma DMAIC approach combined with welding-specific process controls can effectively enhance automotive welding quality and support sustainable defect prevention.